Breast cancer with diabetes insipidus - Dogan, M.; Karakilic, E.; Oz, I.I.; Zorlu, F.; Akbulut, H. (Experimental Oncology, 2008)
Diabetes insipidus (DI) is a rare clinical condition, which is usually caused by neurohypophyseal or pituitary stalk infiltration in cancer patients. Case report: we present a 62-year old metastatic breast cancer woman with DI. She admitted to the hospital because of nausea, vomiting, polyuria and polydipsia, while she was on no cytotoxic medication. She had no electrolyte imbalance except mild hypernatremia. The CT scan of the brain yielded a suspicious area in pituitary gland. A pituitary stalk metastasis was found on magnetic resonance imaging (MRI) of pituitary. Water deprivation test was compatible with DI. A clinical response to nasal vasopressin was achieved. Conclusions: Cancer patients who have symptoms such as nausea, vomiting, polyuria and polydipsia while they are not on chemotherapy should be evaluated for not only metabolic complications like hypercalcemia but also posterior pituitary or stalk metastasis MRI could be the choice of imaging for pituitary metastasis. Несахарный диабет (DI) — редкое клиническое состояние, вызываемое инфильтрацией нейрогипофизарной ножки или
ножки гипофиза у онкологических больных. Описание случая: в исследовании рассмотрен случай выявления DI у 62-летней
женщины, у которой был выявлен рак молочной железы с наличием метастазов. Она поступила в больницу с симптомами
тошноты, рвоты, полиурии и полидипсии, хотя не проходила курса химиотерапии. У больной не выявлено дисбаланса
электролитов, кроме небольшой гипернатриемии. Компьютерная томография мозга показала подозрительную область
в мозговом придатке. На магнитно-резонансном изображении выявлен метастаз в ножке гипофиза. Обезвоживание также
соответствовало диагнозу DI. Получен клинический ответ на назальный вазопрессин. Выводы: онкологические больные
с симптомами тошноты, рвоты, полиурии и полидипсии, не проходящие курса химиотерапии, должны быть обследованы
не только на предмет метаболических осложнений, таких как гиперкальциемия, но и на возможное наличие метастазов
в ножке и задней части гипофиза с помощью магнитно-резонансного изображения.
Ключевые слова: рак, несахарный диабет, метастаз в гипофизе.